Precious metal catalyst for CO oxidation and preparation method thereof

By using catalysts of corrugated plate skeletons and precious metal Pt active components in the sintering process of steel plant, the problems of insufficient activity and short life of existing catalysts under high airspeed conditions are solved, and efficient CO oxidation and mechanical stability are achieved, meeting the strict requirements of industrial applications.

CN119701937APending Publication Date: 2025-03-28SHANXI PULI ENVIRONMENT ENG CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411903533.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing CO oxidation catalysts are insufficient in activity and have a short life under high aerial speed conditions, which cannot meet the strict requirements for CO waste gas treatment in the sintering process of steel plants.

Method used

The noble metal catalysts used as corrugated plates as the framework material, precious metal Pt as the active component, and TiO2 and SiO2 as the support are used. The specific preparation methods include multiple coatings, low-temperature drying, and high-temperature roasting techniques to improve the adhesion and activity of the catalyst.

Benefits of technology

The catalyst has excellent oxidation activity on CO emission gas under 260°C, and the CO conversion rate can reach more than 92%. It has excellent mechanical stability and long life, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a noble metal catalyst for CO oxidation and a preparation method thereof, and belongs to the technical field of industrial waste gas treatment. According to the catalyst, a corrugated plate is used as a framework material, precious metal Pt is used as an active component, and TiO2 and SiO2 are used as carriers. The specific preparation method comprises the following steps: step 1, taking deionized water, putting the deionized water into a stirrer for stirring, and sequentially adding a dispersing agent 1; 2, adding titanium dioxide, and continuously stirring; adding ammonia water to adjust the pH value of the slurry; 3, adding silica sol, and adding a platinum nitrate solution; continuously stirring; 4, adding a dispersing agent 2 into the mixed slurry, and continuously stirring to obtain uniform catalyst slurry; 5, dipping the corrugated plate into the catalyst slurry to ensure that the catalyst slurry fully infiltrates the surface of the corrugated plate; after dipping is completed, the corrugated plate is taken out and naturally aired; step 6, drying; and 7, roasting to prepare the noble metal catalyst for CO oxidation. The catalyst has excellent mechanical stability and efficient CO oxidation performance, and the preparation process of the catalyst is energy-saving and environment-friendly. The catalyst adopts a corrugated plate as a framework material, has high mechanical strength and durability, and is suitable for long-term use under a high airspeed condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial waste gas treatment, and specifically relates to a noble metal catalyst for CO oxidation and a preparation method thereof. Background Art

[0002] With the increasingly stringent industrial emission standards, the large amount of CO waste gas generated in the sintering process of steel mills urgently needs to be effectively treated. CO is a toxic gas that has adverse effects on human health and the environment. In view of the large amount of CO waste gas emissions in the sintering process of steel mills, the existing CO oxidation catalysts often have problems of insufficient activity and short life under high space velocity conditions, and cannot meet the strict requirements of industrial applications for environmental emissions. Therefore, it is urgent to develop an efficient, stable and industrially suitable CO oxidation catalyst. Therefore, the development of an efficient CO oxidation catalyst is of great significance. Summary of the invention

[0003] The purpose of the present invention is to solve the above problems existing in the existing sintering process of steel plants and to provide a noble metal catalyst for CO oxidation.

[0004] Another object of the present invention is to provide a method for preparing the catalyst.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] The present invention is a noble metal catalyst for CO oxidation, the catalyst uses a corrugated plate (made of corrugated paper) as a skeleton material, noble metal Pt as an active component, and TiO2 and SiO2 as carriers;

[0007] The precursor of the active component Pt is platinum nitrate, TiO2 comes from titanium dioxide, and SiO2 comes from silica sol. Titanium dioxide and silica sol are both common chemical materials in industry with high stability and good dispersibility.

[0008] The method for preparing a noble metal catalyst for CO oxidation of the present invention comprises the following steps:

[0009] Step 1: Take 5970-8070g of deionized water, place it in a blender and stir, and add 312g of dispersant 1 thereto in sequence to evenly disperse the titanium dioxide in the water;

[0010] Step 2: Add 3315-4485g of titanium dioxide and continue stirring for 5 minutes; then, add 200-270g of 25% ammonia water and adjust the pH value of the slurry to 8-9;

[0011] Step 3: Add 265-359 g of silica sol and slowly add diluted platinum nitrate solution to make the platinum content reach 0.2%-0.3% of the total weight of the slurry; continue stirring for 2-3 hours to ensure uniform composition;

[0012] Step 4: Add 34 g of dispersant 2 to the mixed slurry to increase the viscosity of the slurry, and continue stirring for 12 hours to obtain a uniform catalyst slurry;

[0013] Step 5: Slowly immerse the corrugated plate cut to a size of 150mm×150mm×200mm into the prepared catalyst slurry, and keep the immersion state for 50 seconds to ensure that the catalyst slurry fully infiltrates the surface of the corrugated plate; after the immersion is completed, slowly take out the corrugated plate and suspend it in the air to discharge the excess slurry that cannot adhere under the action of gravity and external force; then, naturally dry the coated corrugated plate for 5 hours;

[0014] Step 6: Dry the corrugated board obtained in step 5 at 120°C for 3 hours to complete the first coating and drying; then carry out the second coating, air-drying and drying treatment in the same manner;

[0015] Step 7: Finally, the coated corrugated plate was calcined at 540°C for 2 hours to obtain the precious metal catalyst for CO oxidation.

[0016] A further preferred solution is that the material of the corrugated board is corrugated paper.

[0017] Further preferred solution: the dispersant 1 preferably uses polyether silicone oil or polypropylene alcohol, which has good dispersibility and can effectively disperse titanium dioxide evenly in water, thereby improving the stability of the catalyst slurry.

[0018] Further preferred solution: the dispersant 2 adopts an organic sulfonic acid or organic carboxylic acid surfactant, preferably a non-ionic dispersant (P-2), which is mainly used to increase the viscosity of the slurry, thereby improving the uniformity and adhesion during the coating process.

[0019] The present invention has the following beneficial effects:

[0020] The present invention aims at the condition that the amount of CO waste gas discharged in the sintering process of steel plants is large, and prepares a precious metal catalyst that meets the requirements of CO oxidation. The catalyst has the following excellent properties:

[0021] (1) Excellent mechanical stability. The catalyst uses corrugated plate as the skeleton material, which has high mechanical strength and durability and is suitable for long-term use under high space velocity conditions.

[0022] (2) High-efficiency CO oxidation performance: The catalyst prepared by the present invention has excellent oxidation activity for CO exhaust gas from the sintering plant of a steel plant at 260°C, and the CO conversion rate can reach more than 92%.

[0023] (3) The catalyst preparation process is energy-saving and environmentally friendly. Multiple coatings, low-temperature drying, and high-temperature calcination techniques are used in the preparation process to improve the adhesion and activity of the catalyst and reduce overall energy consumption. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below with reference to specific embodiments:

[0025] Example 1

[0026] Step 1: Take 7020g of deionized water and place it in a blender for stirring, gradually add 312g of dispersant 1 (used to evenly disperse titanium dioxide in water), and stir evenly.

[0027] Step 2: Add 3900g of titanium dioxide under stirring and continue stirring for 5 minutes to ensure that the titanium dioxide is fully dispersed. Then slowly add 234g of ammonia water and stir for 10 minutes to adjust the slurry pH to 8-9.

[0028] Step 3: Add 312 g of silica sol, stir evenly, and then slowly add diluted platinum nitrate solution (so that the platinum content reaches 0.3% of the total weight of the slurry). Continue stirring for 2-3 hours until a uniform slurry is formed.

[0029] Step 4: Add dispersant 2 (used to increase the viscosity of the slurry) and continue stirring for 12 hours to obtain a uniform catalyst slurry.

[0030] Step 5: Apply the catalyst slurry evenly on the surface of the cut corrugated plate (size 150mm×150mm×200mm) and dry it naturally for 5 hours.

[0031] Step 6: Dry at 120°C for 3 hours. After drying, apply the slurry for the second time, dry naturally for 5 hours again, and dry at 120°C for 3 hours.

[0032] Step 7: calcine the dried corrugated plate at 540°C for 2 hours to obtain the final catalyst.

[0033] Example 2

[0034] Step 1: Take 6000g of deionized water and place it in a blender, add 312g of dispersant 1, and stir evenly.

[0035] Step 2: Gradually add 3900g titanium dioxide, stir for 5 minutes, and after uniform dispersion, add 234g ammonia water to adjust the slurry pH to 8-9.

[0036] Step 3: Add another 312 g of silica sol, and slowly add the diluted platinum nitrate solution (adjust the platinum content to 0.2% of the total weight of the slurry), and stir for 2-3 hours to form a uniform slurry.

[0037] Step 4: Add 34 g of dispersant 2 and continue stirring for 12 hours to ensure the slurry is uniform.

[0038] Step 5: Apply the mixed slurry evenly on the corrugated board, dry it for 5 hours, and then dry it at 120°C for 3 hours. Repeat the coating steps, dry it again, and dry it.

[0039] Step 6: Finally, calcining at 540°C for 2 hours to obtain the catalyst.

[0040] Comparative Example 1

[0041] Step 1: 7020 g of deionized water was placed in a mixer and stirred without adding dispersant 1. 3900 g of titanium dioxide was directly added, and after stirring for 5 minutes, 234 g of ammonia water was added to adjust the pH of the slurry to 8-9.

[0042] Step 2: Add 312 g of silica sol, slowly add diluted platinum nitrate solution (control the platinum content to be 0.3% of the total weight of the slurry), and stir for 2-3 hours to form a slurry.

[0043] Step 3: Without adding dispersant 2, the prepared slurry is directly used to coat the corrugated board. The coating method is direct brushing without the dipping step. After coating, it is naturally dried for 5 hours.

[0044] Step 4: Dry at 120°C for 3 hours, and then calcine at 540°C for 2 hours to obtain the final catalyst.

[0045] Example 3

[0046] Step 1: Take 6822g of deionized water and place it in a blender for stirring, and then add 312g of dispersant 1 in sequence to make the titanium tungsten powder evenly dispersed.

[0047] Step 2: Add 4215g of titanium tungsten powder (the content of tungsten oxide is 5%), stir for 5 minutes, and then add 256g of ammonia water to adjust the pH of the slurry to 8-9.

[0048] Step 3: Add 359 g of silica sol, slowly add platinum nitrate solution (platinum content is 0.3% of the total weight of the slurry), and stir for 2-3 hours until a uniform slurry is formed.

[0049] Step 4: Add dispersant 2 and stir for 12 hours to obtain catalyst slurry.

[0050] Step 5: Apply the catalyst slurry to the surface of the corrugated plate, dry it naturally for 5 hours, and then dry it at 120°C for 3 hours, and repeat the coating and drying steps.

[0051] Step 6: Finally, calcine at 540°C for 2 hours to obtain the catalyst.

[0052] Example 4

[0053] Step 1: Take 7020g of deionized water, put it in a blender, add 312g of dispersant 1, and disperse the titanium dioxide evenly.

[0054] Step 2: After adding 3750g of titanium dioxide, stir for 5 minutes, and add 248g of ammonia water to adjust the slurry pH to 8-9.

[0055] Step 3: Add 150g of clay, stir evenly, then add 280g of silica sol and continue stirring for 10 minutes.

[0056] Step 4: slowly add platinum nitrate solution (the platinum content is 0.3% of the total weight of the slurry), stir for 2-3 hours, then add dispersant 2, and stir for 12 hours to prepare catalyst slurry.

[0057] Step 5: Evenly apply the catalyst slurry on the surface of the cut corrugated board, dry it for 5 hours, and then dry it at 120°C for 3 hours. Perform the second coating and drying process.

[0058] Step 6: Finally, the corrugated plate was calcined at 540°C for 2 hours to obtain the catalyst.

[0059] Example 5

[0060] Step 1: Add 8070g of deionized water into a blender, add 312g of dispersant 1 in sequence, and stir until evenly dispersed.

[0061] Step 2: Add 4200g of titanium dioxide and stir for 5 minutes, then add 224g of ammonia water to adjust the pH to 8-9.

[0062] Step 3: Add 285g of silica sol and stir evenly, then slowly add 1040g of anhydrous tin chloride and stir for 30 minutes to ensure sufficient mixing.

[0063] Step 4: slowly add the diluted platinum nitrate solution (so that the platinum content reaches 0.3% of the total weight of the slurry), stir for 2-3 hours, add dispersant 2, and continue stirring for 12 hours to form a catalyst slurry.

[0064] Step 5: Evenly coat the catalyst slurry on the corrugated board, dry it for 5 hours, and then dry it at 120° C. for 3 hours. Repeat the coating and drying steps.

[0065] Step 6: Finally, the catalyst was calcined at 540° C. for 2 hours. The catalyst showed the best performance in the CO oxidation test, and maintained high activity and stability after long-term operation, and was the catalyst with the longest life in all examples.

[0066] Comparative Example 2

[0067] Step 1: Add 8070g of deionized water into a blender, add 312g of dispersant 1 in sequence, and stir until evenly dispersed.

[0068] Step 2: Add 4200g of titanium dioxide and stir for 5 minutes, then add 234g of ammonia water to adjust the pH to 8-9.

[0069] Step 3: Add 285g of silica sol and stir evenly, then slowly add 1040g of anhydrous tin chloride and stir for 30 minutes to ensure sufficient mixing.

[0070] Step 4: Instead of using platinum nitrate as the active component, use the same weight of silver nitrate (AgNO3) solution to adjust the silver content to 0.3% of the total weight of the slurry. After stirring for 2-3 hours, add dispersant 2 and continue stirring for 12 hours to form a catalyst slurry.

[0071] Step 5: Evenly coat the catalyst slurry on the corrugated board, dry it for 5 hours, and then dry it at 120° C. for 3 hours. Repeat the coating and drying steps.

[0072] Step 6: Finally, calcine at 540°C for 2 hours to obtain the catalyst.

[0073] Description of the above comparative proportions:

[0074] (1) Comparative Example 1 Compared with Example 1 and Example 2, Dispersant 1 and Dispersant 2 were not used in the preparation process.

[0075] (2) Comparative Example 2 Compared with Example 5, the precious metal platinum is replaced by silver as the active component.

[0076] Description of the above embodiments:

[0077] (1) The main difference between Example 1 and Example 2 is the content of precious metal platinum (Pt). In Example 1, the content of platinum accounts for 0.3% of the total weight of the slurry, while in Example 2, the content of platinum is reduced to 0.2%.

[0078] (2) The difference between Example 3 and Example 1 lies in the choice of carrier material. Example 1 uses titanium dioxide (TiO2) as a carrier, while Example 3 uses titanium-tungsten powder (Ti-W) instead.

[0079] (3) The main difference between Example 4 and Example 1 is that 150 g of clay additive is added during the preparation process. The addition of clay significantly improves the structural stability and heat resistance of the catalyst.

[0080] (4) Compared with Example 1, Example 5 further added 1040 g of anhydrous tin chloride (SnCl2) as an auxiliary agent after adding the silica sol.

[0081] The performance indicators of the catalysts prepared in the above examples and comparative examples are as follows:

[0082] project Example 1 Example 2 Comparative Example 1 Example 3 Example 4 Example 5 Comparative Example 2 CO conversion efficiency (%) 94 92 61 95 96 99 38

Claims

1. A noble metal catalyst for CO oxidation, characterized in that: The catalyst uses corrugated plate as the skeleton material, noble metal Pt as the active component, and TiO2 and SiO2 as the carrier; The precursor of the active component Pt is platinum nitrate, TiO2 comes from titanium dioxide, and SiO2 comes from silica sol. Titanium dioxide and silica sol are both common chemical materials in industry.

2. The method for preparing a noble metal catalyst for CO oxidation according to claim 1, characterized in that: The following steps are involved: Step 1: Take 5970-8070g of deionized water, place it in a blender and stir, and add 312g of dispersant 1 thereto in sequence to evenly disperse the titanium dioxide in the water; Step 2: Add 3315-4485g of titanium dioxide and continue stirring for 5 minutes; then, add 200-270g of 25% ammonia water and adjust the pH value of the slurry to 8-9; Step 3: Add 265-359 g of silica sol and slowly add diluted platinum nitrate solution to make the platinum content reach 0.2%-0.3% of the total weight of the slurry; continue stirring for 2-3 hours to ensure uniform composition; Step 4: Add 34 g of dispersant 2 to the mixed slurry to increase the viscosity of the slurry, and continue stirring for 12 hours to obtain a uniform catalyst slurry; Step 5: Slowly immerse the corrugated plate cut to a size of 150mm×150mm×200mm into the prepared catalyst slurry, and keep the immersion state for 50 seconds to ensure that the catalyst slurry fully infiltrates the surface of the corrugated plate; after the immersion is completed, slowly take out the corrugated plate and suspend it in the air to discharge the excess slurry that cannot adhere under the action of gravity and external force; then, naturally dry the coated corrugated plate for 5 hours; Step 6: Dry the corrugated board obtained in step 5 at 120°C for 3 hours to complete the first coating and drying; then carry out the second coating, air-drying and drying treatment in the same manner; Step 7: Finally, the coated corrugated plate was calcined at 540°C for 2 hours to obtain the precious metal catalyst for CO oxidation.

3. The method for preparing a noble metal catalyst for CO oxidation according to claim 1 or 2, characterized in that: The material of the corrugated board is corrugated paper.

4. The method for preparing a noble metal catalyst for CO oxidation according to claim 1 or 2, characterized in that: The dispersant 1 is preferably polyether silicone oil or polypropylene alcohol.

5. The method for preparing a noble metal catalyst for CO oxidation according to claim 1 or 2, characterized in that: The dispersant 2 is an organic sulfonic acid or organic carboxylic acid surfactant, and a non-ionic dispersant (P-2) is preferred.

Citation Information

Cited By

  • Carbon monoxide oxidation catalyst and preparation method thereof

    CN120189956A